Morphometric characterization of Oryzaephilus Surinamensis L. (Coleoptera: Silvanidae) reared in different type of grains - Abdul, Nurul Huda; M, Noor Amni (Universiti Kebangsaan Malaysia, 2020)
The host on which Oryzaephilus surinamensis choose to lay eggs and multiply can have a great influence on their development. In this study, morphometric characterization has been used to measure size variability of this insect pest reared in different types of culture and verify whether the food preference has an impact on the morphology of the insect. Measurement of body length, body width at the widest point, head width, length of antenna, length of thorax and length of hind femur of 3rd generation of saw-toothed grain beetle from four cultures; barley, rice, oat groat and dried maize were measured using stereoscopic microscope equipped with LAS EZ imaging software. All data were analyzed using IBM SPSS. The present morphometry study showed significant differences between populations thus proved that food preference or host range choices play important role in development and growth of the insect. Significant differences were recorded for body length (F = 8.250), body width at the widest point (F = 4.620), and head width (F = 4.300) at P < 0.05 among the cultures. Thus, body length, body width at the widest point, and head width were the most suitable measurements to be used in observing the effect of food on O. surinamensis biological growth.